2021
DOI: 10.3390/ijms22136952
|View full text |Cite
|
Sign up to set email alerts
|

NAC Transcription Factor PwNAC11 Activates ERD1 by Interaction with ABF3 and DREB2A to Enhance Drought Tolerance in Transgenic Arabidopsis

Abstract: NAC (NAM, ATAF1/2, and CUC2) transcription factors are ubiquitously distributed in eukaryotes and play significant roles in stress response. However, the functional verifications of NACs in Picea (P.) wilsonii remain largely uncharacterized. Here, we identified the NAC transcription factor PwNAC11 as a mediator of drought stress, which was significantly upregulated in P. wilsonii under drought and abscisic acid (ABA) treatments. Yeast two-hybrid assays showed that both the full length and C-terminal of PwNAC11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…The results of this study are consistent with results of previous works. Apart from that, it has been shown that NACs interact with DREB transcription factors [34,43,44]. The RcNAC72-RcDREB2A interactions in rose were demonstrated through experiments.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The results of this study are consistent with results of previous works. Apart from that, it has been shown that NACs interact with DREB transcription factors [34,43,44]. The RcNAC72-RcDREB2A interactions in rose were demonstrated through experiments.…”
Section: Discussionmentioning
confidence: 96%
“…In wheat, TaABRE2 bound to the ABRE cis-acting element on the TaNAC48 promoter, indicating that TaNAC48 was involved in the ABA signaling pathway in response to drought stress in wheat [21]. PwNAC11 could interact with ABF3 to improve drought tolerance in transgenic Arabidopsis [34]. In addition, studies have elaborated that NAC TFs have regulatory relationships with DREB TFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant NAC is derived from the acronym NAM (no apical meristem) cloned from Petunia hybrida in 1996 [16] and ATAF1/2 and CUC2 (cup-shaped cotyledon) cloned from Arabidopsis thaliana [17]. Numerous studies show that NAC plays important roles in plant growth and development, response to stress, and other processes [16][17][18][19][20][21][22][23]. Rose (Rosa hybrida) RhNAC100 regulates the expression of genes related to cell elongation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, grapevine (Vitis vinifera) VviNAC33 facilitates the transition from a vegetative to mature phase by inducing leaf degreening and growth cessation [19], and FaRIF is a key regulator of strawberry fruit ripening from early developmental stages by controlling abscisic acid biosynthesis and signaling, cell wall degradation and modification, the phenylpropanoid pathway, volatile production, and the balance of aerobic/anaerobic metabolism [20]. Moreover, Picea wilsonii PwNAC11 plays a dominant role in plants that respond positively to early drought stress [21]. However, relatively few studies have been conducted on NAC in relation to loquat.…”
Section: Introductionmentioning
confidence: 99%